The role of diversity-themed poster media in promoting tolerance character development in religious education among junior secondary school students - Rahma Yanthi (Jurnal Inovasi Guru Indonesia, 2025)
Background: Tolerance character development represents a critical component of religious education in multicultural societies where students encounter diverse beliefs and cultural backgrounds. Schools require innovative instructional strategies to internalize tolerance values effectively within classroom learning processes. Visual media, particularly diversity-themed posters, offer potential pedagogical advantages in strengthening moral reflection and inclusive attitudes among adolescents. Objective: This study aimed to examine the effectiveness of diversity-themed poster media in promoting tolerance character development among junior secondary school students in religious education. Methods: A quasi-experimental pretest–posttest control group design was employed involving 72 Grade VIII students from a public junior secondary school. Participants were divided into an experimental group receiving a six-week diversity-themed poster intervention and a control group receiving conventional instruction. Tolerance character was measured using a validated 25-item Likert-scale instrument covering five dimensions: respect for differences, openness to dialogue, empathy, non-discrimination, and cooperative behavior. Data were analyzed using descriptive statistics, paired sample t-tests, independent sample t-tests, and effect size calculations. Results: Baseline analysis indicated no significant difference between groups prior to the intervention (p > 0.05). The experimental group demonstrated a statistically significant increase in tolerance scores from pretest to posttest (p < 0.001), while the control group showed no significant improvement (p > 0.05). Posttest comparison revealed a significant difference between groups (p < 0.001) with a large effect size (Cohen’s d = 0.92), indicating substantial intervention impact. Conclusion: Diversity-themed poster media significantly enhance tolerance character development in junior secondary religious education. The integration of visually engaging and value-oriented instructional materials supports moral internalization and fosters inclusive attitudes in multicultural classroom settings.